2013
DOI: 10.1002/hep.26251
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte nuclear factor 4 alpha deletion promotes diethylnitrosamine-induced hepatocellular carcinoma in rodents

Abstract: HNF4α, the master regulator of hepatocyte differentiation, has been recently shown to inhibit hepatocyte proliferation via unknown mechanisms. We investigated the mechanisms of HNF4α-induced inhibition of hepatocyte proliferation using a novel TAM-inducible, hepatocyte specific HNF4α knockdown mouse model. Hepatocyte specific deletion of HNF4α in adult mice resulted in increased hepatocyte proliferation with a significant increase in liver to body weight ratio. We determined global gene expression changes usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
163
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(188 citation statements)
references
References 56 publications
12
163
1
3
Order By: Relevance
“…Previous studies involving inducible HNF4a deletion support of our findings (Bonzo et al, 2012;Walesky et al, 2013). When re-analyzing the microarray and RNA sequencing data we found that hepatocyte-specific deletion of HNF4a in adult mice resulted in upregulation of many Wnt target genes including Myc, Ccnd1 (cyclin D1), Vegf, Sox9, Egfr and Jun.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies involving inducible HNF4a deletion support of our findings (Bonzo et al, 2012;Walesky et al, 2013). When re-analyzing the microarray and RNA sequencing data we found that hepatocyte-specific deletion of HNF4a in adult mice resulted in upregulation of many Wnt target genes including Myc, Ccnd1 (cyclin D1), Vegf, Sox9, Egfr and Jun.…”
Section: Discussionsupporting
confidence: 87%
“…Hepatocyte-specific deletion of Hnf4α results in hepatocellular dedifferentiation and proliferation and promotes chemically induced hepatocarcinogenesis. These responses were accompanied by upregulation of the promitogenic genes Egr1, Myc, and Ccnd1 (17,(56)(57)(58), which were also detected in Slu7-depleted mice. Interestingly, CCND1 can also interfere with HNF4α transcriptional activity (57), while increased c-Myc levels modulate the switch in GLS1 and GLS2 expression (38) and, through the induction of hnRNPA1, can promote the expression of HK2 and PKM2 favoring glycolytic metabolism (38, 59).…”
Section: Discussionmentioning
confidence: 86%
“…Specifically, he is focusing on potential interactions between the Wnt/β-catenin pathway and hepatocyte nuclear factor 4 alpha (HNF4α), molecules that are involved in the development of the liver as well as CCA (35)(36)(37)(38)(39)(40). Studies in the laboratory have shown that knockdown of HNF4α in the zebrafish leads to a reduction in hepatocyte differentiation while genetic or chemical increase in β-catenin results in a loss of HNF4α and a maintenance of cholangiocyte differentiation.…”
Section: Ccf Grant Recipient Talksmentioning
confidence: 99%